2012
DOI: 10.1111/j.1471-4159.2012.07939.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition of research focus from vasospasm to early brain injury after subarachnoid hemorrhage

Abstract: Subarachnoid hemorrhage is a devastating disease that can be difficult to manage. Not only is the initial bleeding and rebleeding associated with high mortality, but a large fraction of patients also develop a delayed neurological deficit even when the aneurysm was successfully secured with clipping or coiling. Past research effort has traditionally been focused on vasospasm, which was conceived to be the sole factor for delayed neurological deficit. The failure of anti-vasospastic drugs to improve outcome in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 146 publications
0
98
0
Order By: Relevance
“…58,[66][67][68] Acute hypoperfusions are attributed to reversible microvasoconstriction in a rat model of mTBI, 69 and acute vasoconstriction has been reported within an hour after TBI in human survivors with subarachnoid hemorrhage. 70,71 Further, even transient hypoperfusion may produce prolonged changes in cortical thickness as evidenced by decreased cortical thickness and less fMRI activation in rats at 4 months after a single episode of hypoxia-ischemia. 72 Future studies that simultaneously measure cortical thickness and perfusion at an early stage after mTBI may shed light on this relationship.…”
Section: Early Cortical Thinning In Mtbi Survivors After Mvcsmentioning
confidence: 99%
“…58,[66][67][68] Acute hypoperfusions are attributed to reversible microvasoconstriction in a rat model of mTBI, 69 and acute vasoconstriction has been reported within an hour after TBI in human survivors with subarachnoid hemorrhage. 70,71 Further, even transient hypoperfusion may produce prolonged changes in cortical thickness as evidenced by decreased cortical thickness and less fMRI activation in rats at 4 months after a single episode of hypoxia-ischemia. 72 Future studies that simultaneously measure cortical thickness and perfusion at an early stage after mTBI may shed light on this relationship.…”
Section: Early Cortical Thinning In Mtbi Survivors After Mvcsmentioning
confidence: 99%
“…3 In a clinical setting as well, brain edema on CT was reported to be an independent risk factor for mortality and poor outcome following SAH. 5 Many molecules, such as blood breakdown products and inflammatory mediators, may be involved, either acting simultaneously or at different stages during BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological scores (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) were assessed by summing 6 test scores (spontaneous activity; spontaneous movement of 4 limbs; forepaw outstretching; climbing; body proprioception; and response to whisker stimulation), as previously described. 8 A beam balance test investigated the animal's ability to walk on a narrow wooden beam for 60 seconds: 4 points, walking ≥ 20 cm; 3 points, walking ≥ 10 cm but < 20 cm; 2 points, walking ≥ 10 cm but falling; 1 point, walking < 10 cm; and 0 points, falling while walking < 10 cm.…”
Section: Neurobehavioral Testmentioning
confidence: 99%
“…More recently, mechanisms of early brain injury have moved center stage in the research focus. It has been suggested that these mechanisms evolve with time and contribute to the path-ogenesis of DCI [3,4]. The rupture of an aneurysm and consequent release of blood into the subarachnoid space leads to an abrupt increase of the intracranial pressure (ICP), which is suggested to cause a brief cerebral perfu-sion arrest [4].…”
Section: Introductionmentioning
confidence: 99%